Orientation dependent interface morphology and oxide stability in a commercial niobium alloy: Explaining experimental results with density functional theory. (1st May 2022) - Dhole, Ashish; Bhattacharya, Amrita; de Kloe, René; Gupta, Rohit Kumar; Gokhale, Amol A.; Samajdar, I.
Abstract: The metal-oxide interface of a commercial niobium (Nb) alloy showed clear presence of 'hills' and 'plateaus' on the metallic side. This interface morphology was orientation-dependent and appeared to determine the presence of the surrounding oxide phase(s). In particular, the hills were associated with non-(111) Nb crystallographic orientations. The corresponding oxide phase was mostly tetragonal Nb2 O5, which also contained significant porosities. Oxide phases around the plateaus, on the other hand, were primarily orthorhombic Nb2 O5 . In addition, the oxygen (O) concentrations also differed on the metallic side of the hills and plateaus, the latter showing a sharper compositional gradient. Density functional theory (DFT) calculations were performed to explain the experimentally observed orientation dependence and oxide stability. The calculations showed that (111)-Nb grains not only had the highest surface energy ( ESurface ) and O adsorption energy ( EAds ), but also had the highest activation energy barrier for O diffusion. On the other hand, the tetragonal Nb2 O5 was energetically stable at higher O partial pressure. An analytical model, based on O adsorption and short-range diffusion at the metal-oxide interface, was proposed. This study not only related the experimental results with DFT simulations, but also provided an atomistic framework to interface-controlled oxidation in a commercial Nb alloy. Graphical abstract: Image, graphical abstract